1978
DOI: 10.1063/1.325265
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surface recombination on current in AlxGa1−xAs heterojunctions

Abstract: Articles you may be interested inInfluence of structural defects on carrier recombination and current gain in an InGaAs/AlGaAs/GaAs heterojunction phototransistor Emitter composition and geometry related surface recombination current of AlGaAs/GaAs heterojunction bipolar transistors Mesa surface recombination current in AlGaAs/GaAs heterojunction bipolar transistors with an emitter-base-emitter structure Effect of oxygenimplant isolation on the recombination leakage current of np + AlGaAs graded heterojunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(66 citation statements)
references
References 24 publications
3
61
0
2
Order By: Relevance
“…The parameters J 0 2PER and J 02 both have an effect at low voltages; however, several studies in GaAs [16][17][18][19] show that the amplitude of the recombination current with ideality factor n = 2 does not correlate with the area; instead, it correlates with the perimeter. A previous study of degradation in GaAs solar cells revealed changes in the I-V curve at low voltages [8]; consequently, Table 1 Dimensions of the diodes of GaAs used in the study of the recombination current at low voltages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters J 0 2PER and J 02 both have an effect at low voltages; however, several studies in GaAs [16][17][18][19] show that the amplitude of the recombination current with ideality factor n = 2 does not correlate with the area; instead, it correlates with the perimeter. A previous study of degradation in GaAs solar cells revealed changes in the I-V curve at low voltages [8]; consequently, Table 1 Dimensions of the diodes of GaAs used in the study of the recombination current at low voltages.…”
Section: Resultsmentioning
confidence: 99%
“…From these figures it can be inferred that, as expected, at low voltages the current correlates with the area in agreement with Refs. [16][17][18][19]. Therefore, I 02 is smaller than / 0 2PER.…”
Section: Explanation For the Dark I-v Curve In Gaas Solar Cellsmentioning
confidence: 99%
“…U s is the rate of surface recombination that is proportional to the excess carrier density at the surface, (n(R) À n i ), with a proportionality constant S called the surface recombination velocity. The perimeter recombination current per unit length is found by integrating the surface recombination current density qU s along the direction perpendicular to the junction, over the surface of the active region (or the effective surface diffusion length (L s ), which can be approximated by the active layer thickness for thin (< 0.1 lm) active layers 23 ) where the carrier density at the surface is assumed to be constant along the surface of the active region. Multiplying and dividing by the excess carrier density in the bulk (n(0) À n i ) and using n(0) ¼ n i exp (qV/gkT), the saturation part of the above equation for current density can be written as…”
Section: B Diffusion Modelmentioning
confidence: 99%
“…In fact, any depleted surface near the bordering pn-junction can lead to severe J 02 -type recombination, due to efficient transport of charge-carriers through the highly doped p-and n-type regions towards this recombination active region. [12] The recombination at the depleted surface near the pn-junction can be about one order of magnitude higher than the recombination current in the depletion region of the junction. [12] Secondly, adjacent highly doped n-and p-type Si regions can induce a tunneling recombination current between the conduction band of n + Si and the valence band of p + Si.…”
Section: Introductionmentioning
confidence: 99%
“…[12] The recombination at the depleted surface near the pn-junction can be about one order of magnitude higher than the recombination current in the depletion region of the junction. [12] Secondly, adjacent highly doped n-and p-type Si regions can induce a tunneling recombination current between the conduction band of n + Si and the valence band of p + Si.…”
Section: Introductionmentioning
confidence: 99%